The risk of chronic obstructive pulmonary disease in patients with rheumatoid arthritis: a real-world cohort study from 136,821 patients - Kang, Tianlun; Xi, Yajing; Liu, Xiaoping; Qian, Tangliang; Lu, Siyi; Li, Leqing; Liu, Zhi; Wei, James Cheng-Chung; Hou, Xiujuan (Frontiers in Immunology, 2025)
ObjectiveTo compare the risk of chronic obstructive pulmonary disease (COPD) between patients newly diagnosed with RA and individuals without RA. This large-scale study aims to provide novel insights into the association between RA and COPD by evaluating the impact of clinical factors and medications on COPD risk, using robust propensity-score matching.MethodsThis retrospective comparative cohort study utilized data from the TriNetX Research Network, collected on October 9, 2023. Patients newly diagnosed with RA from 2010 to 2021 were compared to non-RA individuals matched on demographics and medical history. Propensity-score matching balanced baseline covariates. The primary outcome was the 5-year risk of newly onset COPD (ICD-10: J41-J44), analyzed using Kaplan-Meier and Cox’s proportional hazards models.ResultsThe study included 136,820 pairs of RA and non-RA patients. The 5-year cumulative probability of COPD was 7.36% in the RA cohort versus 5.97% in the non-RA cohort, with a hazard ratio of 1.228 (95% CI = 1.186-1.272). Subgroup analyses showed higher COPD risk in RA patients across different demographics and clinical factors. Males, older patients, higher rheumatoid factor, and higher erythrocyte sedimentation rate increased COPD risk, while DMARDs and systemic NSAIDs reduced it.ConclusionRA patients have a significantly higher risk of developing COPD compared to non-RA individuals. These findings underscore the importance of targeted COPD prevention and management in RA patients.